PENGARUH KAFEIN TERHADAP PENINGKATAN FUNGSI EKSEKUTIF PADA MAHASISWA KEDOKTERAN - Florencia Adeline,* Bernadius Realino Harjanto,* Yuda Turana,* Nelly Tina Widjaja* (NEURONA, 2016)
INTRODUCTION EXECUTIVE FUNCTION IS AN UMBRELLA OF COGNITIVE FUNCTIONS AND HAS AN IMPORTANT ROLE IN MEDICAL STUDENTS SEVERAL RESEARCHES SHOW THAT CAFFEINE IMPROVES COGNITIVE FUNCTION BUT THE IMPACT OF CAFFEINE ON EXECUTIVE FUNCTION IS NOT WELL UNDERSTOOD